Situation of Child Domestic Workers in Bangladesh (Global Journal of Management and Business Research, 2014)
This study examines the situation of child domestic workers and attitude of child specialist about child domestic work towards ILO new standards of decent work for domestic workers among 120 child domestic workers in five selected areas of Dhaka city and 15 child specialists from five different groups. The study has been employed both qualitative and quantitative method. Findings of this study revealed that the education level of child domestic workers is very poor and the major portion (79.2 per cent) has no access to non formal education. The promising things were found by the study that (75.83 per cent) child domestic workers wish to go school and continue their study. Almost all (73.3 per cent) did not get any full day off during the week and (21.7 per cent) CDWs get rest breaks 3-4hours and alarming thing is found that (19.2 per cent) did not get any opportunity to take rest during the day.
Keywords: child domestic workers; education; child protection; ilo standards